PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS EKSPERIMEN TERHADAP HASIL BELAJAR IPA MATERI PERUBAHAN ENERGI SISWA KELAS V SDN RAJAPOLAH - Nurkiat Aisyah Wulandari; Sunanih; Mohammad Fahmi Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
In science learning in class V SDN Rajapolah, students' understanding is still lacking. This is because in terms of learning, it shows that there is minimal use of learning models in the classroom. So this study aims to determine the effect of the Project Based Learning learning model based on experiments on science learning outcomes in the material on energy changes for class V SDN Rajapolah students. his type of research is quantitative research. The research method used is Quasi Experimental with Nonequivalent Control Group Design. The population used is 76 students of grade V SDN Rajapolah. The sample used is a simple random sampling technique. Namely class VA with 38 students as the control class and class VB with 38 students as the experimental class. The data collection technique used is a test technique using multiple choice questions. Based on the results of the study, it was found that there was an influence of the use of the Project Based Learning learning model based on experiments on the learning outcomes of science on energy changes in grade V students of SDN Rajapolah. This can be seen from the difference in the average posttest score of the control class, which was 69.45, while the average posttest score of the experimental class was 83.37. In the hypothesis test, an Independent Sample T-Test was carried out which obtained a significance value (2-tailed) of 0.000 <0.05. So it can be concluded that H1 is accepted and H0 is rejected. This shows that there is a significant difference between the posttest results of the experimental class using the project based learning model and the control class without using the project based learning model.